Self‐healing materials for structural applications. Issue 4 (7th June 2013) - Guadagno, L.; Raimondo, M.; Naddeo, C.; Longo, P.; Mariconda, A.
<x xml:space="preserve">Abstract</x> Self‐healing materials for structural applications offer considerable practical benefits because they would allow to overcome the difficulties connected to damage diagnosis and repair. In this article, a process active at very low temperature for the repair of damaged structural material is shown. The self‐repair function is based on the metathesis polymerization of ENB activated by Hoveyda–Grubbs' first generation catalyst. The self‐healing epoxy mixture, containing the catalyst powder allows a cure temperature up to 180°C. Dynamic mechanical analysis was used to determine mechanical parameters. The autorepair composite shows a high modulus in a wide temperature range, a glass transition temperature at about 100°C and a self‐healing efficiency of about 95%. POLYM. ENG. SCI., 54:777–784, 2014. © 2013 Society of Plastics Engineers